Natural Frequency Analysis for Hydropower Structure - Radzi M.R.; Zawawi M.H.; Yusairah W.N.; Mazlan A.Z.A.; Abas A.; Zainol M.R.R.M.A. (Springer, 2023)
A dam normally serves the main purpose of retaining water. However, the uncertainties vibration affected from the internal and external sources of the dam such as the flow of water vibration of the hydropower mechanical machine and other related sources has increased the insecurity of the dam structure. In this study, one of the oldest hydroelectric dams in Malaysia which are Chenderoh Dam in Kuala Kangsar, Perak is taken to analyze and discuss the structural dynamic analysis. The analysis has been investigated on the sector gate, right bank, intake and bottom outlet section of the dam structure. The actual size of structures (1:1) for each section has been modeled into the CAD software based on real build-in materials. Finite element (FE) model is constructed with the required boundary condition and meshing sensitivity analysis. From the result, the natural frequency values and mode of shapes are determined for all the section but, only significant value will be shown in this paper. The highest value of natural frequency occurred is 5.09Hz at sector gate, 52.3Hz at left bank, 11.73Hz at right bank, 2.76Hz at intake and 9.00Hz at bottom outlet. In addition, from the frequency response friction (FRF) graphs show the highest deflection frequently occurred at x-axis direction for sector gate, right bank, bottom outlet, left bank and intake. All of these values must be taken into consideration before any failure happens at the dam. 2020, Springer Nature Singapore Pte Ltd.